MANAJEMEN PERUBAHAN DI MADRASAH: STRATEGI ADAPTIF DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM DI MADRASAH IBTIDAIYAH (MI) MUHAMMADIYAH REJANG LEBONG - Susanti, Deli; Warlizasusi, Jumira; Kholilah Harahap, Emmi; Destriani, Destriani (At-Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study explores adaptive strategies in change management implemented by madrasahs as Islamic educational institutions to enhance educational quality. Faced with challenges such as globalization, technological advancement, and socio-cultural shifts, madrasahs must transform institutionally while maintaining their Islamic identity. Employing a descriptive qualitative method and a case study at Madrasah Ibtidaiyah (MI) Muhammadiyah Rejang Lebong, the research investigates the driving forces, barriers, and implementation strategies of change. The findings indicate that successful change management relies on transformational leadership, stakeholder engagement, and a strong commitment to Islamic values. These adaptive strategies enable madrasahs to stay relevant and competitive within the national education system. The study contributes to the discourse on Islamic educational reform by offering practical insights into sustainable and value-based organizational transformation.